Effect of quercetin or butylated hydroxytoluene on cooled or frozen-thawed ram sperm quality - Canuto, Lucas Emanuel Ferreira [UNESP]; Segabinazzi, Lorenzo Garrido Teixeira Martini [UNESP]; De Araújo, Endrigo Adonis Braga [UNESP]; Silva, Luis Fernando Mercês Chaves [UNESP]; De Oliveira, Sidnei Nunes [UNESP]; Dalanezi, Felipe Morales [UNESP]; Dell'Aqua, José Antonio [UNESP]; Papa, Frederico Ozanam [UNESP]; Oba, Eunice [UNESP] (Universidade Estadual de Londrina, 2022)
Cooling and freezing processes cause physical and chemical damage to sperm by cold shock and oxidative stress. This study aimed to evaluate the effect of two antioxidants on sperm parameters of cooled and frozen-thawed ram semen diluted in an egg yolk-based extender. Semen was collected from 30 rams and processed in two consecutive experiments to test the inclusion of different concentrations of quercetin and butylated hydroxytoluene (BHT) in an egg yolk-based semen extender. Dimethyl sulfoxide (DMSO) was added as a solvent to the semen extender in a ratio of 1 mL DMSO for 90 mg of quercetin and 1 mL DMSO for 880 mg of BHT. After collection, semen was diluted at 200 × 106 motile sperm/mL (control) and split into different groups in each experiment. In experiment 1, semen was diluted with the extender containing quercetin (Q5, 5 μg/mL; Q10, 10 μg/mL; Q15, 15 μg/mL) or DMSO alone (DMSO1, 0.055 μL DMSO per mL; DMSO2, 0.165 μL DMSO per mL). In experiment 2, semen was diluted with the extender with BHT (BHT1, 0.5 μg/mL; BHT2, 1 μg/mL; BHT3, 1.5 μg/mL) or DMSO alone (DMSO3, 0.375 μL DMSO per mL; DMSO4, 1.125 μL DMSO per mL). After dilution, the semen was divided into two aliquots. Treated ram sperm samples were also subjected to different storage methods. The first set of samples was cooled at 5°C for 24 h, whereas the second set of samples was frozen-thawed. Sperm motility parameters and plasma membrane integrity (PMI) were evaluated immediately after dilution (0h) and 24 h after cooling and in the frozen-thawed samples via computer-assisted sperm analysis and epifluorescence microscopy, respectively. The inclusion of quercetin or BHT did not affect sperm motility parameters or PMI of fresh, cooled, or frozen-thawed sperm in this study (P < 0.05). However, further studies are needed to test the effects of these antioxidants on the fertility of cryopreserved ram semen.
Keywords: Antioxidant; Cryopreservation; Lipid peroxidation; Oxidative damage; Sheep; Small ruminants